Raptors Mortality in Northwest Rajasthan, India (2017–2022) - Dau L. Bohra; Maha S. Rao (Пернатые хищники и их охрана)
A major contributing factor in declining populations of vultures is believed to be the widespread use of drugs such as Diclofenac, once commonly-used as a livestock anti-inflammatory drug. Use of Diclofenac is now banned in India. However, during the last 3 years, vulture’s death cases are increasing not only in Rajasthan but also in other parts of India. From 2017–2022, totally 791 vultures of 3 species i.e. Eurasian Griffon Vulture (Gyps fulvus), Cinereous Black Vulture (Aegypius monachus) and Egyptian Vulture (Neophron percnopterus), and 231 Steppe Eagle (Aquila nipalensis) were found dead at Jorbeer dumping site.